Intermetallic Compounds Formation during 316L Stainless Steel Reaction with Al-Zn-Si Coating Alloy - Abdul Khaliq; Abdulaziz S. Alghamdi; Mohamed Ramadan; Tayyab Subhani; Wajdi Rajhi; Waseem Haider; Mohammad Mehedi Hasan (Crystals, 2022)
Steel products are coated with Aluminum (Al) and Zinc (Zn) alloys to improve their corrosion properties. Bulk steel products are coated in batches; however, steel sheets are coated by a continuous hot-dip galvanizing process. Steel sheets are guided into and out of the molten Al-Zn-Si (AZ) bath with the help of stainless-steel rolls, known as guiding, and sink rolls. These rolls are subjected to excessive surface corrosion with molten AZ bath and, hence, are replaced frequently. The surface deterioration of the immersed rolls has been a long-standing issue in the galvanizing industry. In this study, 316L stainless-steel (SS) rods are immersed in the AZ alloy at 600 °C. The immersion time varied from 1 day to 7 days under the static melt conditions in the iron (Fe)-saturated AZ bath. Microstructural analysis of the immersed SS samples revealed two distinct intermetallic compound (IMC) layers forming between the SS substrate and AZ alloy. The IMC layer 1 (AL-1) formed between the SS substrate and IMC layer 2 (AL-2), growing in thickness from 68 µm to 120 µm within 5 days of immersion. The AL-2, which formed between AL-1 and AZ alloy after 24 h of immersion, then grew in thickness up to 150 µm with an uneven trend. The AL-1 is composed of Fe2Al5 and that of AL-2 is composed of FeAl3 that were predicted by the FactSage thermodynamic analysis. Crack development between AL-1 and AL-2 layers, and disintegration of AL-2 into the AZ bath, are key findings of this study. A drastic hardness increase was observed because the IMC layers produce a hard and brittle sink roll surface.